Public Perception of the Negative Impact of Covid-19 Vaccination in Sidoarjo - Asiyatul Ulfiyah; Didik Hariyanto (Universitas Muhammadiyah Sidoarjo, 2023)
This research is based on the fact that many people do not believe and doubt the existence of vaccination for various reasons such as issues regarding health, vaccine development, the impact of vaccines and the effectiveness of vaccine types, causing different perceptions from each community. This study uses a qualitative research type with a descriptive approach. The technique of determining the informants in this study used a purposive sampling technique. The results of this study indicate that the perception of the Pucanganom community can be seen from three elements, namely the first Perception Perpetrator, from the results of this study it can be seen that most of the Pucanganom Village community accept the Covid-19 vaccination because vaccination is quite important in avoiding the Covid-19 virus and his party believes and enthusiasm with the Covid-19 vaccination. The second in terms of targets or objects, shows that they believe vaccination can prevent the transmission of the Covid-19 virus. Of the many types of vaccinations available, the people of Pucanganom Village believe that moderna vaccination is the best type of vaccination. The third, in terms of the situation, shows that the people of Pucanganom Village in carrying out vaccinations on their own consciousness, not through coercion. They realized the importance of vaccination from various socializations carried out by village officials. Information regarding vaccination in Pucanganom Village is clear, complete and adequate. In practice, these three elements show a good perception of the pucangnaom community regarding the Covid-19 vaccination.